PELATIHAN PENGOLAHAN MI BERBAHAN BAKU LOKAL (UBI KAYU) BAGI MASYARAKAT BINAAN DINAS PANGAN BONE BOLANGO - Desi Arisanti; adnan engelen (UPPM Politeknik Gorontalo, 2020)
Cassava is a local material that can be used as a type of processed food that is used for daily consumption. One of them is processed cassava noodle products. Utilization is for public consumption every day so it does not experience dependence on flour-based noodles. In addition, the nutritional content of cassava-based noodles that we consume daily can be more diverse and well fulfilled. The problem often faced is that not many people carry out activities for processing cassava products into cassava noodle products. That causes saturation for consumption. The several solutions that will be carried out consist of three stages, namely 1) Socialization of the benefits of processing local materials such as cassava into cassava noodle products, 2) Training on the manufacture of cassava noodle products. The hope after this PKM activity is that the community or the group supported by the Bone Bolango Food Service can understand and be skilled in processing local materials and improve the quality of high-value processed noodle products in the market and improve the economic welfare of the community